Kinetic investigation of para-nitrophenol reduction with photodeposited platinum nanoparticles onto tunicate cellulose. Issue 48 (28th October 2022) - Thiel, T. A.; Zhang, X.; Radhakrishnan, B.; van de Krol, R.; Abdi, F. F.; Schroeter, M.; Schomäcker, R.; Schwarze, M.
Abstract : Modified cellulose (ModCe) was used in a photodeposition process as a support material for platinum nanoparticles. The supported catalysts were investigated for the transfer hydrogenation of para -nitrophenol (PNP) to para -aminophenol (PAP). Abstract : Photodeposition is a specific method for depositing metallic co-catalysts onto photocatalysts and was applied for immobilizing platinum nanoparticles onto cellulose, a photocatalytically inactive biopolymer. The obtained Pt@cellulose catalysts show narrow and well-dispersed nanoparticles with average sizes between 2 and 5 nm, whereby loading, size and distribution depend on the preparation conditions. The catalysts were investigated for the hydrogenation of para -nitrophenol via transfer hydrogenation using sodium borohydride as the hydrogen source, and the reaction rate constant was determined using the pseudo-first-order reaction rate law. The Pt@cellulose catalysts are catalytically active with rate constant values k from 0.09 × 10 −3 to 0.43 × 10 −3 min −1, which were higher than the rate constant of a commercial Pt@Al2 O3 catalyst ( k = 0.09 × 10 −3 min −1 ). Additionally, the Pt@cellulose catalyst can be used for electrochemical hydrogenation of para -nitrophenol where the hydrogen is electrocatalytically formed. The electrochemical hydrogenation is faster compared to the transfer hydrogenation ( k = 0.11 min −1 ).